Domesticated Animals on Exhibit at the Museum of Comparative Zoology, 1900–1928. Issue 1 (March 2019) - Tonn, Jenna
Highlights: The Museum of Comparative Zoology's domesticated animals exhibit revealed links between genetics, animal fancying, and experimental breeding. Fancy poultry from Charles B. Davenport and guinea pigs illustrating Mendelian inheritance from William E. Castle proved surprisingly popular. This exhibition modernized the natural history museum, which was still aligned with its founder Louis Agassiz's views against evolution. Abstract: In 1905 the Museum of Comparative Zoology at Harvard University began planning for a new domesticated animals exhibition in honor of the 100th anniversary of the birth of its founder Louis Agassiz. The resulting displays of variation and heredity in poultry, pigeons, rabbits, mice, and guinea pigs proved surprisingly popular to museumgoers. Some of these specimens still exist in the museum's storage facilities, namely a series of poultry donated by the biologist Charles B. Davenport and an elaborate set of guinea pigs from the experimental evolutionist William E. Castle. Situating these domesticated animal displays within academic and popular cultures of poultry fancying, animal breeding, and evolutionary science reveals how a nineteenth-century museum known for its ties to anti-evolutionary principles attempted to modernize its public exhibits.